COMPARATIVE EVALUATION OF S. MUTANS AND C. ALBICANS SURFACE ADHESION AND MECHANICAL STRENGTH AS OPERATIONAL CHARACTERISTICS OF MATERIALS FOR TEMPORARY FIXED DENTURES - Fastovets, O.O.; Kotelevskyi, R.A.; Matviyenko, R.Yu. (World of Medicine and Biology, 2018)
We carried out the comparative study of 7 materials, regarding the intensity of adhesion on their surfaces of S. mutans and C. albicans, using colorimetric analysis, and assessment of their mechanical properties according to indicators of fracture strength.It has been established that under using the S. mutans suspension, the highest indices of optical density, corresponding to the intensity of surface bacterial adhesion, were detected for Acryloxid (19.71 ± 2.59) and Carbodent (19.08 ± 2.23), and they decreased in the following sequence: Tempolat C (12.33 ± 1.58), Structur Premium (10.78 ± 1.92), Protemt 4 (8.92 ± 1.62), Visalys Temp (6.82 ± 1.97), Telio CS c & b (4.68 ± 1.65) (p < 0.05). For C. albicans, the maximum optical density values were recorded for Acryloxid (58.35 ± 9.03) and Carbodent (51.90 ± 8.31) and respectively decreased for Tempolat C (35.45 ± 5.13), Structur Premium (30.45 ± 5.34), Protemt 4 (31.65 ± 8.29), Telio CS c & b (30.60 ± 8.93), Visalys Temp (20.10 ± 7.09) (p < 0, 05). The indices of fracture strength were significantly lower for the plastics of Acryloxid (745.23 ± 94.75 N) and Carbodent (711.09 ± 179.18 N) compared to bis-acrylic composites such as Tempolat C (973.71 ± 98.46), Protemt 4 (1009.08 ± 84.50), Structur Premium (1392.19 ± 224.11 N), Visalys Temp (1254.38 ± 156.35 N), while the highest force was registered for the polyurethane composite Telio CS c & b (1106.45 ± 134.65 N) (p